PENGARUH MODEL PEMBELAJARAN KONTEKSTUAL DAN MEDIA KONGKRET TERHADAP HASIL BELAJAR IPA KELAS V DI SEKOLAH DASAR - Ana Cinde Karnasih; Sugilar Gandasasmita; Yuyun Elizabeth Patras (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of the contextual teaching and learning (CTL) model supported by concrete media on science learning outcomes of fifth-grade students of SDN Mekarsari, Bekasi. The research method used was a quasi-experiment with a nonequivalent control group design. The sample consisted of 67 students, divided into an experimental class (34 students) and a control class (33 students), selected by purposive sampling. The experimental class used the CTL learning model with concrete media, while the control class used conventional learning methods. Data collection was carried out through observation, pretest-posttest, and questionnaires. Data were analyzed using SPSS Version 21, with normality, homogeneity, N-Gain, and t-test tests. The results showed that there was a significant difference between student learning outcomes in the experimental class and the control class. The average N-Gain value in the experimental class was 44.52%, higher than the control class of 29.22%. The t-test confirmed a significant difference (p <0.05) between the two groups. These findings indicate that the application of contextual learning models with concrete media is effective in improving students' science learning outcomes.